2021
DOI: 10.1007/s11259-021-09791-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional value and microbiological safety in commercial dog food

Abstract: In addition to properly balancing nutritional value in accordance with the needs of a dog, estimating the microbiological quality of dog food is crucial in providing healthy and safe foods. The aim of this study was to examine the quality of dry food for adult dogs, with particular reference to: (1) evaluating the nutritional value and compliance with nutritional guidelines for dogs, (2) comparing the nutritional value of dog foods, with particular emphasis on the division into cereal and cereal-free foods, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Consistent with the individual results of the E-tongue and the E-nose, the multivariate analysis results did not show significant difference between domestic and international products or difference by protein source. Currently, multivariate analysis is used to evaluate dog foods in various research fields [ 9 , 40 ]. In a study by Alegría-Morán et al, the PCA of the 10-year food preference database was used to relate dogs’ food choices with nutritional composition of the diets, and it was found that the content of crude fiber and dry matter negatively associated with dogs’ food preferences [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the individual results of the E-tongue and the E-nose, the multivariate analysis results did not show significant difference between domestic and international products or difference by protein source. Currently, multivariate analysis is used to evaluate dog foods in various research fields [ 9 , 40 ]. In a study by Alegría-Morán et al, the PCA of the 10-year food preference database was used to relate dogs’ food choices with nutritional composition of the diets, and it was found that the content of crude fiber and dry matter negatively associated with dogs’ food preferences [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Alegría-Morán et al, the PCA of the 10-year food preference database was used to relate dogs’ food choices with nutritional composition of the diets, and it was found that the content of crude fiber and dry matter negatively associated with dogs’ food preferences [ 40 ]. The PCA analysis was also used to distinguish dog foods according to the similarity of the nutritional profile of the group [ 9 ]. Recent studies have shown that multivariate analysis of E-nose data can distinguish the aroma of beef and pork [ 41 ] and classify the aroma profile of beef according to quality grade [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat meals are often used due to their high-protein content and are obtained by the rendering process [ 37 , 38 ]. The lack of respect for good pet food manufacturing and handling practices [ 39 , 40 ] could result in a favorable condition for the growth of microorganisms capable of decarboxylation processes [ 41 , 42 , 43 ]. BAs can therefore be an alarm bell for possible microbial contaminations as they can occur in the final product as a result of microbial decarboxylation processes; this has been observed in dry dog chews and feeds, in sealed packages and in bulk [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial pet food contains over 10% crude fat [ 17 ], which is more than that in pig feed [ 18 ]. Previously, in animal research, pigs were the most used animals to study the in vitro simulation of digestion.…”
Section: Introductionmentioning
confidence: 99%